Political Policy Implementation Analysis Kupang City Regional Income And Expenditure Budget (Study On The Budget For Managing Covid-19 In 2021) - Esrah D.N.A. BENU; Yefta Y.M. SABAAT; Akhmad SYAFRUDDIN; JOSEF KANISIUS BAU (International Journal of Environmental, Sustainability, and Social Science, 2022)
The issue of COVID-19 has affected the economy and society of the country. So the government is taking various steps to prevent it by pushing laws of isolation and quarantine, as well as enforcing restrictions and community activities (PPKM). This study aims to clarify the analysis, policy, and political budget handling of COVID-19 in Kupang City. Research methodology is qualitative, with the type of cases used to study and analyze situations affecting individuals and groups dealing with COVID-19 in great detail. According to research findings, the Kupang city government has relocated its budget and refocused on regulating COVID-19 through Regional Regulation Number 3 of 2020 on the regional allocation of Kupang City Year 2021 budget as described by Regulation Mayor (Perwali) Kupang. The letter number 98 revised return becomes the Guardian Number 5 of 2021 Regarding Modifications to Regulations Mayor Kupang Number 98 of 2020 Regarding Explanation Budget Kupang City Regional Income and Expenditure. The Kupang city government received funds through policy total of 80,051,530,953 that were entered into Shopping Not Expected (BTT) for natural and artificial disasters (covid19 handling). From the side, implementation policy causes the spread of Covid-19 to be handled slowly since data information is not synchronized with the number of cases in the field. The policy has not held Covid-19 in Kupang City effectively because of the Kupang City DPRD's insufficient political control, the government's responsiveness, the Prosecutor's Team's aggressiveness toward the Covid-19 task force, and public compliance.